Impact of the coronavirus (COVID-19) disease pandemic on healthy lifestyle behaviors in persons with and without disabilities in Qatar - Pandiyan, Uma; Sathian, Brijesh; Kariyathankavil, Ibin; Saad, Rafat; Al Kuwari, Fatma; Alexander, Poovathoor Joseph; Hanif, Saquib; Zabat, Loubna (Frontiers in Psychiatry, 2024)
Purpose This study aimed to examine the impact of the COVID-19 pandemic on the lifestyle behaviors which included physical activity, sedentariness, healthy eating habits, sleep habits, and tobacco use in persons with and without disabilities in Qatar. Methods This cross-sectional study used a structured, online questionnaire. The collected data included demographics, mental health, physical health, eating habits, body weight, sleep, and nicotine intake. This study was conducted between September 25, 2020, and December 31, 2020. Results Seventy respondents from Qatar participated in the study. Pre-pandemic healthy lifestyle behaviors (physical activity, healthy diet, sleep, etc.) showed no significant differences between people with and without disabilities. However, perceived changes in mental and physical health and eating habits during the pandemic lockdown differed between people with and without disabilities. People with disabilities reported worsening mental health (64.7%), physical health (53%), and dietary habits compared to the pre-pandemic levels. Furthermore, the more severe the disability, the more significant is its impact on mental and physical health. Conclusion This study indicated that the pandemic has had a significant impact on the mental and physical health of people with and without disabilities in Qatar. These findings reveal how closely individuals with disabilities and their lifestyle choices are related to their mental and physical well-being. This will enable the development of specific interventions for similar situations in the future.